How does regular exercise affect internet addiction level in university students? - Ç.V. Koçak (Physical Education of Students)
Purpose : The internet is one of the most important technological developments of the era. Internet usage rate is increased rapidly. This intensity of use is thought to cause some behavior disorders in people. In this study, it was aimed to determine the internet addiction status of university students and to evaluate the relationship between regularly exercise and academic achievement. Material : The study group is consisted 50 [n=25 female, n=25 male] university students. The mean of the age of participants was 21.47 [±1.66]. Data was collected by personal information form and Internet Addiction Test. SPSS 22 program was used in the analysis of the obtained data and Shapiro-Wilk Test was applied to determine whether the data showed normal distribution and the significance level was accepted as p<0.05 in the analyses. Data were normally distributed. Paired-Samples T-Test was used to analyze of the data. Results : As the main hypothesis of the study, there was a significant difference between regularly exercise and internet addiction. Also, it was seen that the internet usage period of the participants who exercise regularly decreased. Conclusions : Doing regular exercise can reduces the level of internet addiction and the time spent on the Internet. Regulating and reducing the time spent on the internet can help to protect from psycho-social, physical and physiological negative effects of Internet addiction. It may be suggested to do regular exercise for this. Measures should be taken to reduce and prevent internet addiction of university students. Research can be repeated with different variables in different samples. For example; researches about internet addiction in elite level athletes.